Pathophysiology of Congestion in Heart Failure: A Contemporary Review - Marko Kumric; Tina Ticinovic Kurir; Josko Bozic; Anteo Bradaric Slujo; Duska Glavas; Dino Miric; Mislav Lozo; Jaksa Zanchi; Josip A Borovac (Cardiac Failure Review)
Acutely decompensated heart failure is one of the leading causes of hospitalisation worldwide, with a significant majority of these cases attributed to congestion. Although congestion is commonly mistaken for volume overload, evidence suggests that decompensation can occur without significant water accumulation, being attributed to volume redistribution. Yet, the distinction between intravascular and extravascular congestion in heart failure often blurs, as patients frequently exhibit overlapping features of both, and as patients may transition between phenotypes over time. Considering that differentiation between intravascular and extravascular congestion can lead to different management strategies, the aim of this review was to delineate the pathophysiological nuances between the two, as well as their correlation with clinical, biochemical and imaging indices.